Existence of efficient-equilibrium point of vector optimization - Vilkas, E. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Й. Вилкас. Существование еффективно-равновесных точек в задаче векторной оптимизации E. Vilkas. Vektorinės optimizacijos uždavinio efektyvių-pusiausvyros taškų egzistencija